Numerical processing overcomes left neglect for the greyscales task - Loftus, Andrea; Nicholls, M.; Mattingley, J.; Bradshaw, J. (Lippincott Williams & Wilkins, 2008)
This study examined whether numerical cues affect spatial attention in left neglect. Patients with right parietal damage (four with neglect, three without) completed a dual task. Stimuli consisted of two greyscales overlayed with high numbers (8, 9), low numbers (1, 2) or neutral stimuli (#, &). Participants identified if the overlay was high, low or neutral and then made a relative luminance judgement for the greyscales. Neglect patients demonstrated a rightward greyscales bias in the neutral overlay condition, which was overcome by processing low numbers. Control patients showed a leftward bias in the neutral condition, which was overcome by processing high numbers. The results demonstrate that the spatial architecture of numbers induces shifts of attention, which can overcome left neglect.